Association of sarcopenia with survival in advanced NSCLC patients receiving concurrent immunotherapy and chemotherapy - Bolte, Fabian J.; McTavish, Sloane; Wakefield, Nathan; Shantzer, Lindsey; Hubbard, Caroline; Krishnaraj, Arun; Novicoff, Wendy; Gentzler, Ryan D.; Hall, Richard D. (Frontiers in Oncology, 2022)
Background: Frailty, sarcopenia and malnutrition are powerful predictors of clinical outcomes that are not routinely measured in patients with non-small cell lung cancer (NSCLC). The primary aim of this study was to investigate the association of sarcopenia, determined by the psoas muscle index (PMI) with overall survival (OS) in patients with advanced NSCLC treated with concurrent immune checkpoint inhibitor (ICI) and chemotherapy (CTX). Methods: We retrospectively reviewed data from a cohort of patients with locally advanced or metastatic NSCLC who were treated between 2015 and 2021 at the University of Virginia Medical Center. The cross-sectional area of the psoas muscle was assessed on CT or PET/CT imaging prior to treatment initiation. Multivariate analysis was performed using Cox proportional hazards regression models. Results: A total of 92 patients (median age: 64 years, range 36-89 years), 48 (52.2%) men and 44 (47.8%) women, were included in the study. The median follow-up was 29.6 months. The median OS was 17.8 months. Sarcopenia, defined by a PMI below the 25th percentile, was associated with significantly lower OS (9.1 months in sarcopenic patients vs. 22.3 months in non-sarcopenic patients, P = 0.002). Multivariate analysis revealed that sarcopenia (HR 2.12, P = 0.0209), ECOG ≥ 2 (HR 2.88, P = 0.0027), prognostic nutritional index (HR 3.02, P = 0.0034) and the absence of immune related adverse events (HR 2.04, P = 0.0185) were independently associated with inferior OS. Conclusions: Sarcopenia is independently associated with poor OS in patients with advanced NSCLC undergoing concurrent ICI and CTX.